GAYA KOMUNIKASI CAK DAVE DALAM MEMBENTUK KARAKTERISTIK SUROBOYOAN - Firdaus Azwar Ersyad Firdaus; Chusni Nurlaili Nurlaili Lil Jannah (DAS Institute, 2021)
This study aims to identify and describe in detail and depth the Australian YouTuber Cak Dave's Communication Style in Shaping the Characteristics of Suroboyoan. In this study of communication style, descriptive qualitative research methods use Gerry Philipens Speech Code theory by observing five concepts in the main ideas, including Slang, Intonation, Dialect, Tempo, and Mimic. The sampling technique used in this study was purposive sampling, using 3 sample videos from Cak Dave's YouTube channel, Londo Kampung. The data collection technique was carried out using non-participating observation. Based on the research that has been done, the researcher concludes that the communication style used by Cak Dave as Londo Kampung uses the medok language style and The Structuring Style communication style. Cak Dave uses the Javanese Suroboyoan language with a characteristic that is medok, rude but firm. This language style is complemented by The Structuring Style communication style, where he can plan verbal and non-verbal messages to strengthen his goals further.